The Application of Society Based School and Its Implication toward Self-Governance of the Second Year Students of “SMU ALTERNATIVE QARYAH THAYYIBAH” of Kalibening, Salatiga in the Academic Year of 2007/2008 - Lina Mardliyah (Register Journal, 2008)
This paper attempts to describe the application of society based school and the implication of such a system as well as to depict the relationship between them toward students’ self-governance at SMU Alternative QT in the academic year of 2007/2008. The respondents of the study are 20 students of the second grade and 9 teachers. By applying descriptive qualitative research. It found that there is relationship between the application and the implication of society based school toward the students’ self-governance where the students become more ready to live in the future, realize their own personalities better, and have many skills.Keywords: Society Based School; Self-Governance